2010
DOI: 10.3139/146.110429
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and in-vitro degradation study of electro spun fibrous mat produced from eri silk fibroin

Abstract: Tensile and in-vitro degradation study of electro spun fibrous mat produced from eri silk fibroin Fibrous mat was produced from eri silk fibroin by electro spinning. The fibrous mat was tested for tensile properties and in-vitro bio-degradation by enzymatic treatment. The tensile strength of the mat was 5.3 MPa and its elastic modulus was 49 MPa before bio-degradation. The weight loss obtained after 30 days of degradation was 34 %. The in-vitro enzymatic degradation of fibrous mat was confirmed through Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…Figure 6 shows the degradation of three forms of scaffolds over a period of 15 days by protease XIV. It was observed that the enzymes have etched the surface of the scaffold and degradation was due to surface erosion, which is similar to the findings of Muthumanickkam et al [30]. Due to the degradation of surface, the structure of the scaffold disintegrates.…”
Section: Protease Degradationsupporting
confidence: 84%
“…Figure 6 shows the degradation of three forms of scaffolds over a period of 15 days by protease XIV. It was observed that the enzymes have etched the surface of the scaffold and degradation was due to surface erosion, which is similar to the findings of Muthumanickkam et al [30]. Due to the degradation of surface, the structure of the scaffold disintegrates.…”
Section: Protease Degradationsupporting
confidence: 84%
“…The spectra shows the amide I absorption band at 1659 cm −1 (C=O stretching), amide II absorption band at 1540 cm −1 and 1560 cm −1 (N–H bending), and amide III absorption band at 1379 and 1388 cm −1 (C–N stretching) respectively for the undegummed eri and tasar silks. These absorption bands are attributed to the β-sheet structure of the silk fibroin (Simchuer et al 2010 ; Muthumanickkam et al 2010 ; NasimAmiraliyan and Kish 2009 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 c, d, shows that majority of the pores have diameter in the range of 0.1–2 μm and 1.3–1.5 μm, with mean pore diameter of 0.4 and 1.39 μm respectively for the ethanol treated ESF and TSF scaffolds. When the electrospun mat is immersed in ethanol, it swells and shrinks (Muthumanickkam et al 2010 ; NasimAmiraliyan and Kish 2009 ). The relative shrinkage of nanofibrous scaffolds after treatment leads to decrease in pore diameter and porosity (Thompson et al 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the peak intensity of the ESF-Hap scaffold is less due to the presence of Hap in the ESF-Hap scaffold. The FTIR also shows that the stretch bands pertaining to trifluoroacetic acid (1,100 to 1,200 cm -1 ) used for preparing the polymer solution, which may be allergenic to be used as biomaterial, are not found in the electrospun fibrous scaffolds (Muthumanickkam et al 2010 ). The band absorption in spectrum b (Figure 2 ) at 697, 612, and 563 cm -1 is due to O-P-O bending in the ESF-Hap scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…The optimum concentration of polymer in trifluoroacetic acid was found to be 13% (wt/vol.). The distance between the syringe and the collecting drum was kept at 15 cm, and a 20-kV supply was applied between the syringe and the collecting drum (Muthumanickkam et al 2010 ). The flow rate of the solution was maintained at 1.0 ml/h.…”
Section: Methodsmentioning
confidence: 99%